Implementasi Pembelajaran Hadits-hadits Pendek di RA Al-Azhar Palangka Raya - Afifah, Neela; Rahmasari, Annisa; Mutiara, Arda Sulis; Ma'rifah, Nor; Muzakki, Muzakki (Edu Journal Innovation in Learning and Education, 2024)
Hadith learning is one of the PAI lessons implemented at RA. Hadith learning must be given to young children so that they can grow in accordance with the guidance of Islamic law and can practice commendable qualities. Learning hadiths by memorizing can start with habits carried out at home and in the school environment, and habits that are instilled from childhood bring many benefits to children because hadiths contain hope in the form of moral values ​​and commendable traits. Based on initial observations made by the author at RA Al Azhar, it shows that the superior hadith learning program there is very popular with children, this can be seen from the enthusiasm and joy of the children when taking part in hadith learning. This research aims to obtain an overview of the implementation of learning short Hadiths at RA Al Azhar Palangka Raya. The research method used in this research is descriptive qualitative, while the research subjects are one class B4 and B5 teacher each. Data collection techniques are carried out through observation, interviews and documentation. The research results showed that the hadith taught to students were memorized using the movement method and applied directly by the teacher. Because through this, children will more quickly memorize the hadith and the movements taught, and can apply them in everyday life.